A FREE-MARKET PERSPECTIVE FOR THE PREPARERS AND USERS OF FINANCIAL ACCOUNTING INFORMATION TODAY - Collins, Stuart; White, Gregory (The journal of contemporary issues in business and government, 2006)
This paper explores both academic and professional literature, published over the past few decades, addressing the proliferation of accounting standards and the imposition and increasing burden that has been placed upon the preparers of financial reporting information. The 'pro' argument for increased reporting regulation and disclosure has been the protection of stakeholders; however, recent experiences suggest that this approach has not been entirely successful. A significant number of unexpected corporate collapses have continued to occur. The suggestion is made that, in addition to improved corporate governance and regulation, the interests of stakeholders may be better served through efforts to promote a culture of ethical conduct within the wider business community.